(untitled) (Journal of Bangladesh Academy of Sciences, 2009)
We deal with fuzzy topological spaces, fuzzy compact space, fuzzy S-closed space, fuzzy graph, fuzzy continuous functions and fuzzy LC-continuous functions. In this paper, we introduce the concepts of fuzzy contra-continuities and explore properties and relationships of such types of functions. Keywords: fuzzy contra-continuity, fuzzy S-closed space, fuzzy graph. AMS Subject Classification: 54A40. doi: 10.3329/jbas.v32i1.2444 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 71-77, 2008